Environmental tourism carrying capacity study by using multi criteria evaluation approach in Royal Belum State Park, Perak Darul Ridzuan, Malaysia - Mohd Nayan, Noorul Iffa; Mohd. Din, Shamzani Affendy; Abdullah, Alias; Chee, Hon Loong (IIUM Press, 2011)
Tourism provides opportunities for local regional development but as the brisk growth it exerts pressure on environmental and cultural resources. The environmental problems have reached over the limit of pressure where the natural ecosystem is unable to absorb the stresses of accelerating economic growth and human population rapid growth. Thus, it leads to the evolvement of the term 'sustainability' in any kind of development. Theoretically, tourism needs to be developed which focus on managing and controlling tourism growth pertaining to the capacity of local systems to sustain the growth; a balanced development to meet both needs. Environmental Tourism carrying capacity (ETCC) is regarded to be as a management tool which involves dynamic elements of decision makings on tourist destinations and its consequential elements. The use of Analytic Hierarchy Process (AHP) in this research examines significant indicators which have strong characteristics in scientifically defensible and valuable in management. This paper demonstrates the ETCC survey model by amalgamation of three sources with the deliberation of criteria for indicators selection. The survey model analyses the ecosystem resilience at Royal Belum State Park, Perak Darul Ridzuan, Malaysia. The structural framework proposes to be implemented in demonstrating the limits of environmental tourism carrying capacity at the park.